THE INFLUENCE OF JOB CHARACTERISTICS ON STAFF JOB SATISFACTION OF KUPANG TOURISM ACADEMY - Bekuliu, Roby Yusuf (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
Job satisfaction is the feeling experienced by employees, both pleasant and unpleasant, regarding their work. These feelings are shown through employee behavior, both towards work and everything encountered in the work environment. Job satisfaction is a general attitude shown by staff as a form of assessment of the realities faced in work compared to expected values. Job satisfaction has several dimensions, including: work itself, wages, promotions, supervisors and coworkers. The aim of this research is to describe the influence of job characteristics on the job satisfaction of staff in Kupang Tourism Academy. The results of this research show that job characteristics have an influence on job satisfaction. It can be explained that the staff who work at the Kupang Tourism Academy tend to be interested in the type of work that requires actualization of skills and feedback on what has been done. Therefore, based on the results of this research, it can be suggested to the Kupang Tourism Academyt that there is a need to make efforts to design work in the form of giving varied tasks, to avoid giving the staff a monotonous impression of the task implementation situation, the development of the staff's conditions, including aspects of ability and experience, to delegate the implementation of tasks according to the work capabilities of the staff and provide training opportunities for staff to support their ability to carry out their duties.